Pleiotropic Associations of RARRES2 Gene Variants and Circulating Chemerin Levels: Potential Roles of Chemerin Involved in the Metabolic and Inflammation-Related Diseases - Leay-Kiaw Er; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Yu-Ching Sun; Yu-Lin Ko (Mediators of Inflammation)
Chemerin, an adipokine and inflammatory mediator, is associated with metabolic, inflammation- and immune-mediated diseases. The genetic, clinical, and biomarker correlates of circulating chemerin levels have not been completely elucidated. We analyzed the determinants and correlates of retinoic acid receptor responder 2 (RARRES2; encoding chemerin) gene variants and chemerin levels in the Taiwanese population. In total, 612 individuals were recruited. Clinical and metabolic phenotypes, 13 inflammatory markers, 5 adipokines, and 6 single-nucleotide polymorphisms (SNPs) covering the RARRES2 region were analyzed. High chemerin levels and chemerin level tertiles were positively associated with multiple metabolic phenotypes and circulating inflammatory marker and adipokine levels and negatively associated with high-density lipoprotein cholesterol and adiponectin levels and estimated glomerular filtration rates (eGFRs). Genotype and haplotype analyses showed that RARRES2 SNPs were significantly associated with chemerin, fibrinogen, interleukin 6, and lipocalin 2 levels. Stepwise logistic regression analysis showed that C-reactive protein level, leptin level, triglyceride level, eGFR, rs3735167 genotypes, sex, and soluble P-selectin level were independently associated with chemerin levels. In conclusion, pleiotropic associations were noted between RARRES2 variants, circulating chemerin levels and multiple metabolic phenotypes and inflammatory marker levels. This study provides further evidence for the potential roles of chemerin in metabolic and inflammation-related diseases.